Factors associated with clinically relevant drug-drug interactions with statins in outpatients with coronary artery disease - Nathália Domingos dos Santos, Jéssica; Camila Souza Groia Veloso, Ronara; Silva Tinoco, Marlon; Max Moreira Reis, Adriano (O Mundo da Saúde, 2020)
The concomitant use of statins with other drugs is quite common and contributes to an increased risk of drug interactions that may become manifested clinically as adverse drug reactions. The objective of the study was to determine the factors associated with clinically relevant drug interactions with drug-drug statins in patients seen at the multiprofessional cardiology outpatient clinic of a university hospital. This was a cross-sectional study conducted with 148 patients. The dependent variable was whether or not there were clinically relevant drug interactions with statins according to the Scientific Statement from the American Heart Association. A logistic regression was performed to analyze the association of the occurrence of clinically relevant drug interactions with statins and independent variables. The median number of drugs used was seven (IQR=3) and the number of cardiovascular drugs was five (IQR=2), where 91.2% (n=135) had polypharmacy. The most prevalent diseases in the studied population were systemic arterial hypertension and dyslipidemia. The median number of diseases was five. The prevalence of clinically relevant drug interactions with statins was 43.2%. A positive association was identified between clinically relevant drug interactions with statins and the number of diseases (OR=4.025; CI=1.895-8.553). All potential drug interactions with simvastatin found were of clinical relevance. The most prevalent interactions were: amlodipine + simvastatin and warfarin + simvastatin. The identification of factors associated with drug interactions allows directing measures to prevent adverse events in more exposed populations, such as those with multiple comorbidities.